IDENTIFICATION OF HARD ROCK BASED ON SHALLOW SEISMIC INTERPRETATION AND SPT TEST FOR FOUNDATION OF BRIDGE AT BALANG ISLAND, BALIKPAPAN BAY, EAST KALIMANTAN - Ediar Usman; Kris Budiono (Marine Geological Institute of Indonesia, 2011)
The study area is located in Balikpapan Bay, the connecting waters between Pancur village at the southwest and Balang Island at the northeast. The objective of study is to know the engineering properties of rock as a foundation groundwork of bridge. Result of seismic reflection interpretation profiles in the survey area indicates that the seismic sequences can be divided into two sequences, those are sequence A and B. Sequence A lies at the upper part, which is characterized by concordance, parallel, wavy and hummocky reflectors. Sequence B is characterized by mounded, chaotic and free reflectors. Sediment thickness obtained from seismic profiles show that Quaternary sediment is about 1.56 to 4.89 meters, while harder substrate thickness ranging between 7.03 and 21.60 meters. While, based on core drilling data, hard rock started to appear between 3 and 4 meters below seafloor with Standard Penetration Test (SPT) between 32 and 34 blows as Tertiary sediments. Based on field observation and correlated with geological map of Balang Island, Balikpapan Sheet, the hard rock proposed for base of bridge foundation is Balang Island Formation (Middle Miocene) that consist of claystone, sandstone and coal layers that have been deformated and start to form fold as anticline. The seismic record show that, the hard rock is interpreted as B sequence that underlain by Quaternary sediments. Key words: seismic, drilling, Quaternary sediment, hard rock, bridge foundation, Balang Island Daerah penelitian terletak di Teluk Balikpapan, merupakan perairan penghubung antara desa Pancur di bagian baratdaya dan Pulau Balang di bagian timurlaut. Tujuan penelitian in untuk mengetahui sifat keteknikan batuan keras sebagai tapak jembatan. Hasil interpretasi rekaman seismik di lokasi penelitian menunjukkan bahwa sekuen sedimen dapat dibagi menjadi dua yaitu Sekuen A dan B. Sekuen A terletak di bagian atas dengan ciri reflektor selaras, sejajar, bergelombang terputus-putus dan perlapisan terputus-putus. Bagian paling bawah adalah Sekuen B dicirikan oleh bentuk reflektor berbukit-bukit kecil, berbintik-bintik kacau tidak beraturan dan makin ke bawah dicirikan oleh bebas pantul. Hasil perhitungan ketebalan sedimen pada penampang seismik diperoleh ketebalan sedimen Kuarter antara 1,56 - 4,89 meter dan kedalaman batuan keras berkisar antara 7,03 – 21,60 meter. Sedangkan berdasarkan data pemboran, batuan keras mulai muncul pada kedalaman 3 - 4 meter di bawah dasar laut dengan SPT antara 32 – 34 sebagai sedimen Tersier. Berdasarkan pengamatan di lapangan dan dikorelasikan dengan peta geologi P. Balang, Lembar Balikpapan, batuan keras yang diusulkan sebagai dasar tapak jembatan adalah Formasi Pulau Balang (Miosen Tengah) yang terdiri atas batulempung, batupasir and batubara yang sudah mengalami deformasi dan mulai terlipat membentuk antiklin. Pada penampang seismik, batuan keras tersebut adalah Sekuen B yang ditutupi oleh sedimen Kuarter. Kata kunci: seismik, pemboran, sedimen Kuarter, batuan keras, tapak jembatan, Pulau Balang.